Loop-mediated isothermal amplification (LAMP) – review and classification of methods for sequence-specific detection. Issue 6 (9th January 2020) - Becherer, Lisa; Borst, Nadine; Bakheit, Mohammed; Frischmann, Sieghard; Zengerle, Roland; von Stetten, Felix
Abstract : This comprehensive review provides a systematic classification and a comparative evaluation of current sequence-specific detection methods for LAMP. Abstract : In the course of the last 20 years, isothermal nucleic acid amplification tests have emerged as an important diagnostic tool, not only for clinical applications, but also for food quality control and environmental monitoring. Loop-mediated isothermal amplification (LAMP) is well known for its robust and highly sensitive and specific amplification of target DNA, which is achieved by utilizing up to six primers. Moreover, LAMP excels through its isothermal and energy efficient amplification requirements, rendering it a prime candidate for low-cost diagnostics and analysis at the point of need. Recently, methods for sequence-specific detection have gained more importance because, unlike sequence-independent detection methods, they are highly specific towards the target DNA. In the last 13 years, a variety of sequence-specific methods have emerged, based on a very diverse range of sensing techniques, including optical, magnetic, piezoelectric, electrochemical and magnetoresistive sensing. To give structure to the diverse multitude of sequence-specific methods, we created a systematic classification and provide a critical comparative evaluation according to a catalogue of criteria (analytical performance, multiplexing, quantification and instrumental requirements). Fluorescence-based detection, making up half of the methods, can be processed on open platforms and satisfies all the criteria listed before. Instrumental requirements are discussed in terms of complexity, portability and fluidic cartridges. In addition, the technological readiness level and the kind of platform (open versus method-tailored) are evaluated, the latter playing an important role in the miniaturization and automation of operational process steps. We also observe an increase in the use of smartphone-integrated sensors to improve LAMP-based point-of-need testing. In summary, recent developments in methods for the sequence-specific detection of LAMP demonstrate high potential for many future applications.